1978
DOI: 10.2172/6891041
|View full text |Cite
|
Sign up to set email alerts
|

Light water reactor fuel response during reactivity initiated accident experiments

Abstract: Experimental results from six recent Power Burst Facility (PBF) reactivity initiated accident (RIA) tests are compared with data from previous Special Power Excursion Reactor Test (SPERT), and Japanese Nuclear Safety Research Reactor (NSRR) tests. The RIA fuel behavior experimental program recently started in the PBF is being conducted with coolant conditions typical of hot-startup conditions in a conmercial boiling water reactor. The SPERT and NSRR test programs investigated the behavior of single or small cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Results from these tests have shown that the most important aspect of an RIA or an RIA test, is the magnitude of energy deposited into the fuel [ 7 ]. In RIA experiments of the type carried out in SPERT-CDC and NSRR, the energy deposited near the outside edge of the pellet is the primary heat source for cladding melting, while the energy deposited in the interior of the fuel is not conducted to the cladding surface until after the maximum cladding surface temperature is reached.…”
Section: Results Of Previous Ria Testsmentioning
confidence: 99%
“…Results from these tests have shown that the most important aspect of an RIA or an RIA test, is the magnitude of energy deposited into the fuel [ 7 ]. In RIA experiments of the type carried out in SPERT-CDC and NSRR, the energy deposited near the outside edge of the pellet is the primary heat source for cladding melting, while the energy deposited in the interior of the fuel is not conducted to the cladding surface until after the maximum cladding surface temperature is reached.…”
Section: Results Of Previous Ria Testsmentioning
confidence: 99%
“…This is an indicator that major failure modes for SiC cladding would be principally different from failure modes of the Zr cladding stated in the U.S Code of Federal Regulation, Title 10, Part 50.46, "Acceptance Criteria for Emergency Core Cooling Systems (ECCS) for Light-Water Nuclear Power Reactors" (10 CFR 50.46) [1,12,13] It is worth noting how pervasive the effects of cladding oxidation are in the establishment of the current U.S NRC LOCA criteria. Indeed, the fundamental mechanism of cladding embrittlement of zircaloy during LOCA is due to micro-structural changes of the cladding with oxidation [14,15]. That is, the oxidized cladding cross section exhibits an oxide layer, an oxygen stabilized alpha-phase layer, and a region of prior beta-phase.…”
Section: Current Status Of Sic Cladding Research and Technical Issuesmentioning
confidence: 99%